Targeting of the Protected Group’s Leadership and Otherwise Representative Members as an Indicator of Genocidal Intent - Maksym Vishchyk (Наукові записки НаУКМА: Юридичні науки)
Genocide, i.e., acts committed with the intent to destroy a national, ethnic, religious or racial group, does not require the complete annihilation of every individual member of the group. Instead, genocidal intent can manifest in two forms: to destroy the group in whole or in part. The notion of “partial destruction” remains one of the most complex concepts in the law of genocide. Among other scenarios, it can occur through the destruction of the group’s representative members, selected because of the impact their disappearance would have on the group’s survival. Leaders of the group can qualify as representative individuals; therefore, their complete or partial destruction can be a strong indicator of genocidal intent (the so-called ‘leadership factor’). This article examines the origins and essence of the leadership factor in the law of genocide. Based on the analysis of all international case law relevant to defining the leadership factor, it concludes that the definition of leadership may include various individuals (e.g., political, administrative, religious, cultural, or intellectual figures) who, due to their position or special characteristics, can significantly influence the group’s actions or opinions. The significance of leadership for the group’s functioning and existence, as well as the composition of leadership, will vary depending on the specific protected group targeted for destruction. The article also highlights criticism of the leadership factor by certain commentators for its vague nature, which opens the door to speculative assessment. Finally, the article analyses the loopholes in applying the leadership factor in international jurisprudence and reaches three key conclusions. First, it is important to assess the impact of the leaders’ disappearance on the existence of the group as a social unit, not just the physical survival of its members. Second, although leaders as a standalone category may, in some instances, potentially qualify a substantial part of the group, their destruction more often should be seen as an indicator of an intent to destroy a territorially limited substantial part of the group (e.g., a community), whose substantiality must be assessed in relation to the group as a whole. Third, the finding of genocide does not necessarily require an ex post facto assessment of the impact that the destruction of leaders had on the survival of the group; depending on the context, assessing the potential impact may suffice to evaluate the intent.